2013
DOI: 10.1371/journal.pone.0067762
|View full text |Cite
|
Sign up to set email alerts
|

Six1 Regulates MyoD Expression in Adult Muscle Progenitor Cells

Abstract: Quiescent satellite cells are myogenic progenitors that enable regeneration of skeletal muscle. One of the early events of satellite cell activation following myotrauma is the induction of the myogenic regulatory factor MyoD, which eventually induces terminal differentiation and muscle function gene expression. The purpose of this study was to elucidate the mechanism by which MyoD is induced during activation of satellite cells in mouse muscle undergoing regeneration. We show that Six1, a transcription factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 56 publications
2
55
0
Order By: Relevance
“…Eya1 is the coactivator of Six1 (27, 29), and the Six1/Eya1 complex can bind and regulate MyoD expression (3032). We performed chromatin immunoprecipitation (ChIP) of Six1 and Eya1 at both MyoD and Six1 promoter (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eya1 is the coactivator of Six1 (27, 29), and the Six1/Eya1 complex can bind and regulate MyoD expression (3032). We performed chromatin immunoprecipitation (ChIP) of Six1 and Eya1 at both MyoD and Six1 promoter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4A and B). The latter was used because it is known that Six1 associates with its own promoter (26, 32). Eya1 binding was reduced at MyoD and Six1 genes in the absence of PRMT1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In skeletal muscle, Six1 and Eya1 have been shown to reprogram adult slow-twitch oxidative fibers towards a fast twitch glycolytic 97 and their expression is increased in response to muscle overload 98 . Of note, Six1 is specifically expressed in the satellite cells in skeletal muscle, which are the stem cells within muscle that are important for establishment and regeneration of the tissue 99101 . In adult mice, a conditional knockout of Six1 in this population of cells demonstrated that Six1 was necessary for proper tissue regeneration and replenishment of the stem cell pool following muscle trauma 99 .…”
Section: Opportunities For Targeting the Six1/eya Transcriptional mentioning
confidence: 99%
“…SIX1 expression level is increased in embryogenesis and promotes progenitor cell expansion and survival (6)(7)(8). SIX1 absence results in the reduction in size or loss of numerous organs, as a result of inhibited proliferation and increased apoptosis in mice (9).…”
Section: Introductionmentioning
confidence: 99%